2023
DOI: 10.1177/10608265231209432
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence Victimization Among Refugee Men: Prevalence and Correlates With Associated Factors

Jalal. Kayed Damra,
Mutasem Mohammad Akour,
Mohammad Al Qatawneh

Abstract: This study examined the prevalence of intimate partner violence (IPV) victimization and associated factors among male refugees within a refugee community. A sample of 441 Syrian refugee men from Al- Za'atari refugee camp and other cities was conveniently recruited, and data was collected in 2022 using the revised conflict tactics scale. The findings revealed that psychological IPV was the most prevalent form of abuse, while negotiation, injury, and physical IPV were rare. The age and education level of the men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Evidence came from eight Arab countries. One from Saudi Arabia (Alhalal, 2020), one from Dafur in Sudan (Bennett & de Lacey, 2017), one from Mogadishu in Somalia (Glass et al, 2019), one from Syria (Damra, 2022), two from Occupied Palestinian Territories (Bacchus et al, 2021; Colombini et al, 2020), two from Tunisia (Ben Khelil et al, 2019; Tchaicha & Arfaoui, 2020), four from Egypt (El-Gamal et al, 2022; Mowafy et al, 2020; Samari, 2018; Sayed et al, 2023), and five from the Lebanon (Bartels et al, 2019; El-Khoury & Shafer, 2016; James et al, 2021; Lilleston et al, 2018; Veale et al, 2020). Although these are all Arab countries, they are diverse, each having a mixture of languages, differing cultural beliefs, social structures, laws, living arrangements, and attitudes toward women and range from low economic development to high.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence came from eight Arab countries. One from Saudi Arabia (Alhalal, 2020), one from Dafur in Sudan (Bennett & de Lacey, 2017), one from Mogadishu in Somalia (Glass et al, 2019), one from Syria (Damra, 2022), two from Occupied Palestinian Territories (Bacchus et al, 2021; Colombini et al, 2020), two from Tunisia (Ben Khelil et al, 2019; Tchaicha & Arfaoui, 2020), four from Egypt (El-Gamal et al, 2022; Mowafy et al, 2020; Samari, 2018; Sayed et al, 2023), and five from the Lebanon (Bartels et al, 2019; El-Khoury & Shafer, 2016; James et al, 2021; Lilleston et al, 2018; Veale et al, 2020). Although these are all Arab countries, they are diverse, each having a mixture of languages, differing cultural beliefs, social structures, laws, living arrangements, and attitudes toward women and range from low economic development to high.…”
Section: Resultsmentioning
confidence: 99%
“…Tertiary prevention occurred in seven studies (Damra, 2022; El-Gamal et al, 2022; Lilleston et al, 2018; Mowafy et al, 2020; Sayed et al, 2023; Tchaicha & Arfaoui, 2020; Veale et al, 2020), where women had experienced interpersonal violence (IPV) and interventions educated women about rights, empowerment, and conflict management using a variety of methods. For example, one study used 12 weekly 90-min psychodrama sessions as a therapeutic practice and encouraged participants to use their body to express emotion, rather than verbalize events (Damra, 2022). This study, although small (20 participants), indicated that women participating in the psychodrama sessions displayed significant positive changes in Quality of Life and intimate partner violence, compared to the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation